Z Teorii Odkształceń Wielokrotnych Sprężysto-Plastycznych Ośrodka Stochastycznie Niejednorodnego (Betonu) - Eimer, C. (Engineering Transactions, 1965)
This paper contains a description of a theory of load curves for any loading or unloading process and simultaneous occurrence of elastic and plastic strain. The theory is based on a statistical model composed of perfect elastic-plastic elements, the yield limit Q being variable according to a prescribed probability distribution. Equations are obtained for any loading or unloading branch the form of which depends on the distribution of Q and can be adapted for any experimental diagram. An equation is given for the relative energy loss in a cycle due to internal friction (and approximately proportional to the logarithmic decrement of vibration), it being shown that it depends on the amplitude of vibration. Particular equations are obtained by assuming gamma or multipoint distribution. In the latter case the form of the curve can easily be related with the plastic properties of the medium (e. g. mortar and cement paste).